Management of head and neck injuries A review - P, Deeksheetha; Priyadarshoni S, Sundar; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Head and neck injuries are the most common type of injuries that result in death or comatose in a patient. The management of head and neck injuries in pre hospital and hospital settings have evolved in the past century. For effective management of head and neck injuries a clear knowledge of various causes and mechanisms of head and neck injuries is essential. Timely diagnosis and surgical intervention can prevent catastrophical results. This review focuses on the causes and management of head and neck injuries and how to prevent them.